2021
DOI: 10.1002/anie.202115042
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrogen‐Bonded Ravel Assembled by Anion Coordination

Abstract: Anion-coordination-driven assembly (ACDA) is showing increasing power in the construction of anionic supramolecular architectures.H erein, by expanding the anion centers from oxoanion (phosphate or sulfate) to organic triscarboxylates,a nA rchimedean solid (truncated tetrahedron) and ah ighly entangled, double-walled tetrahedron featuring ar avel topology have been assembled with tris-bis(urea) ligands.T he results demonstrate the promising ability of triscarboxylates as new anion coordination centers in const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 81 publications
0
25
0
Order By: Relevance
“…The self-assembly of tetrahedral (M 3 L 2 ) 4 3 was thus examined with ligands 1b. Aer complexation with CuBF 4 (1.5 equiv., 3.75 mM; 50 C for 30 min) in toluene-d 8 , the formation of 3b was conrmed by 1 H and 13 C NMR (Fig. 2c and S27-S28 †), in addition to 1 H diffusion ordered spectroscopy (DOSY) showing a hydrodynamic diameter of $4.7 nm (log D ¼ À9.8 at 300 K) comparable to that was determined for 3a by X-ray analysis (4.5 nm).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The self-assembly of tetrahedral (M 3 L 2 ) 4 3 was thus examined with ligands 1b. Aer complexation with CuBF 4 (1.5 equiv., 3.75 mM; 50 C for 30 min) in toluene-d 8 , the formation of 3b was conrmed by 1 H and 13 C NMR (Fig. 2c and S27-S28 †), in addition to 1 H diffusion ordered spectroscopy (DOSY) showing a hydrodynamic diameter of $4.7 nm (log D ¼ À9.8 at 300 K) comparable to that was determined for 3a by X-ray analysis (4.5 nm).…”
Section: Resultsmentioning
confidence: 97%
“…As precursor 2 is a $1 : 1 mixture of diastereomers, the relatively rapid interconversion of 2 to 4 by addition of nitrate initially results in the formation of a kinetic mixture of diastereomers of 4d, which is then converted into the thermodynamic product. Cage 4 was characterized by comparing the 1 H and 13 C NMR spectra of 4 (Fig. S12 †) 20 with those of the previously reported 4a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In our previous work, we found that ortho-phenylene spaced oligoureas display strong coordination affinity toward anions, including chloride and oxoanions. [31][32][33] Through multiple hydrogen bonds between urea moieties (NH) and anions, the backbones of oligoureas readily wrap around the bound anions in the centers. As the chain length of oligourea increases, single-strand helical structures are formed by coordinating to two chloride anions.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Wu and co-workers have recently reported an aniontemplated hydrogen-bonded ravel. [12] Fujita and co-workers have also reported examples of entangled architectures with Ag I and tripodal pyridyl ligands, [13] and Nitschke and coworkers have reported tetrahedra (assemblies with four 3way junctions) with unusual topologies. [14] There is a renaissance of topologically complex metallo-interlocked architectures at present, at least in part due to their relative ease of synthesis under thermodynamic control.…”
mentioning
confidence: 99%